Pelatihan Komunikasi Asertif untuk Meningkatkan Pengetahuan Pencegahan Napza pada Siswa Sekolah Menengah Pertama YWKA II Jakarta Timur - Ahmad Rifqy Ash-Shiddiqy; Michiko Mamesah (Jurnal Pengabdian Pada Masyarakat, 2021)
ASSERTIVE COMMUNICATION TRAINING TO IMPROVE DRUGS PREVENTION KNOWLEDGE IN FIRST HIGH SCHOOL STUDENTS OF YWKA II EAST JAKARTA. The high number of drug abuse among students in DKI Jakarta is a big task for Guidance and Counseling Teachers to carry out preventive and curative efforts. The solution offered is to organize an assertive communication training program to increase drug prevention knowledge in students. This research is an experimental study to see the effectiveness of this program carried out at YWKA II East Jakarta junior high school. This study found that the implementation of an assertive communication training program was proven to increase students' knowledge of drug prevention. Based on these results, it is recommended for the government and school leaders to conduct an assertive communication training program to prevent drug abuse in students as a preventive effort that needs to be done early on, especially for junior high school students entering their early teens.